Ferrihydrite nanoparticles as the photosensitizer augment microbial infected wound healing with blue light. Issue 45 (15th November 2021) - Tian, Qing; Yang, Yingchun; Li, Aipeng; Chen, Yao; Li, Yixiao; Sun, Leming; Shang, Li; Gao, Lizeng; Zhang, Lianbing
Abstract : Ferrihydrite nanoparticles (Fhn) as a photosensitizer enhanced the antimicrobial activity and wound healing of blue light, which combined antimicrobial activity, revascularization, and anti-inflammatory effects. Abstract : Visible blue light exerts microbicidal effects with reduced deleterious effects compared with UV light. However, the lack of specific photosensitizers restricts the use of blue light on wound tissues. Here, we report the use of biomimetic ferrihydrite nanoparticles (Fhn) as the sensitizer to augment not only the antimicrobial but also the healing effects of blue light on S. aureus -infected wound tissue. Based on the excellent photo-Fenton active Fhn under blue light illumination (450 nm, 35 630 lux), the Fhn-sensitized blue-light therapy completely cured acute wound within 7 days in sessions of one hour per day and diminished bacterial and fungal colony-forming units more than 5 log (99.999%) and 2 log (99%) in vitro . Mechanistic studies revealed that hydroxyl radicals (˙OH) generated by the combined therapy could effectively damage the microbe genome and membranes without significant damage to wound tissues. Interestingly, these two naturally occurring nonantibiotic modalities (Fhn with blue light) significantly stimulate the angiogenesis and decrease the inflammatory response on the wound site, which accelerates the wound healing synergically. The results demonstrated the use of biomimetic Fhn as the general photosensitizer for enhanced antimicrobial, anti-inflammatory and wound healing effects of blue light-based therapy.